2022
DOI: 10.1002/ptr.7445
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroandrographolide targets CD300f and negatively regulated MRGPRX2‐induced pseudo‐allergic reaction

Abstract: Mas-related G protein-coupled receptor X2 (MRGPRX2) mediates mast cells (MCs) activation, which is a key target for the treatment of allergic diseases. However, there are few drugs targeting MRGPRX2. Leukocyte mono-immunoglobulin-like receptor 3 (CD300f) is a negative regulator of FcεRΙ-mediated MC activation. However, the regulatory effect of CD300f on MRGPRX2 remains unclear. Dehydroandrographolide (DA) is a main contributor of Andrographis paniculata (Burm.f.) Nees (family: Acanthaceae) have been shown to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Most of these exogenous ligands are the molecular basis of MRGPRX2-dependent adverse drug reactions ( 7 , 8 ). Several molecules, such as natural compounds, cytokines, peptides, and DNA aptamers, have been described to prevent MRGPRX2-mediated pseudo-allergic responses and inflammation ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these exogenous ligands are the molecular basis of MRGPRX2-dependent adverse drug reactions ( 7 , 8 ). Several molecules, such as natural compounds, cytokines, peptides, and DNA aptamers, have been described to prevent MRGPRX2-mediated pseudo-allergic responses and inflammation ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wall is a common variety of traditional Chinese medicine (TCM) ( Che et al, 2019 ). It is mainly used for the treatment of upper respiratory tract infection, bronchial asthma, viral pneumonia and diarrhea ( Che et al, 2022 ). Dehydroandrographolide (Deh, Andrographis paniculata (Burm.f.)…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Dehydroandrographolide is a diterpene lactone compound extracted from andrographis. Numerous studies have shown that dehydroandrographolide (DA) has anti-inflammatory, [6,7] anti-allergy, [8,9] antiviral, [10] hepatobiliary protection, [11] and other drug activities. In recent years, it has been found that DA shows effective anti-cancer activity in various cancers, mainly by inhibiting proliferation, promoting apoptosis, and reducing the migration and invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%